PENGARUH PENGGUNAAN MEDIA SOSIAL SEBAGAI SARANA PEMBELAJARAN AGAMA ISLAM PADA ERA REVOLUSI INDUSTRI 4.0 - Ayu Mutiara; Nur Aliyah Septiani Umar; Ria Yuliana Prasojo; Hisny Fajrussalam (Jurnal Al Burhan, 2022)
The development of technology, information, and communication is currently experiencing very rapid progress. The use of Islamic social media in this era can develop Islamic learning strategies. Social media is a tool to facilitate learning and is expected to be able to handle the crisis of Islamic religious knowledge. Aiming to determine the use of social media in Islamic religious learning, this research uses a quantitative approach with a survey method. Data collection used a questionnaire that was distributed to 50 respondents who used social media. The findings from this study indicate that the use of social media has an influence on Islamic religious learning. This can be information to maximize the use of social media or technology in education.